The changes of nutrition labeling of packaged food in Hangzhou in China during 2008-2010. - Shengfeng Wang; Yong Chen; Miao Liu; Zhiheng Hong; Dianjianyi Sun; Yukun Du; Meng Su; Canqing Yu; Qingmin Liu; Yanjun Ren; Jun Lv; Liming Li (PLoS ONE, 2011)
OBJECTIVE: To understand the changes of the nutrition labeling of packaged food in China two years after the promulgation of the Regulation for Food Nutrition Labeling, which encourages food manufacturers to identify nutrition labeling. METHODS: Investigators copied out the nutrition information panel, nutrition claim and nutrient function claim of packaged food in a supermarket with prepared questionnaire and finished normative judgment in 2008 and 2010. RESULTS: 4693 and 5526 kinds of packaged food were investigated separately. Nutrition information panel, nutrition claim and nutrient function claim were found on the food label of 27.6%, 13.0% and 1.9% of packaged food respectively in 2008, while 35.1%, 7.7% and 2.3% in 2010. The nutrition information panel which labeled energy, protein, fat, carbohydrate and sodium was 597 (43.8%) and 1661 (85.9%) in 2008 and 2010, only 134 (9.8%) and 985 (51.0%) nutrition information panel were totally normalized. Nutrition claim and nutrient function claim focused on vitamin, mineral and dietary fiber. The total qualified proportions for nutrition claim were increased significantly for most of the nutrients, except for cholesterol. There were 6 (6.4%) and 5 (3.9%) nutrient function claims with hinting of therapeutic effects on diseases separately. CONCLUSION: Although the voluntary regulation remarkably improved the level of normalization for nutrition labeling, its role on the prevalence was minus. It's imperative to enforce nutrition labeling for not only China but also other countries, and furthermore, health education on nutrition labeling should be initiated to support the policy.